Work volume in strength training is not affected by rest interval strategy - Monteiro, W. D.; Venturim, F. O.; Perez, A. J.; Farinatti, P. T. V. (The Journal of Sports Medicine and Physical Fitness, 2013)
Aim: Between-set rest intervals (RI) may be determined using exercise-recovery-ratio (ERR) or fixed periods. The study investigated the influence of different ERR and fixed RI on the training volume in sessions aiming for hypertrophy with upper-body exercises recruiting different muscle mass (bench press-BP and triceps extension-TE). Methods: Sixteen men (25±2 years, 78±6 kg, 178±5 cm) with previous experience in resistance training performed 5 sets of maximum repetitions in each exercise with five RI protocols (RR1:3 [I3]; ERR1:5 [I5]; ERR1:7 [I7]; increasing ERR [IP] (1:3-1:5-1:7-1:9); 2-min fixed [2F]) in a counterbalanced design. The number of repetitions and work volume (load x repetitions) in each set and along the sessions (load x repetitions x sets) were compared across the RI protocols. Results: The maximum repetitions decreased along with the sets in both exercises, but TE had lower percent decrease compared to BP, due to a longer time to perform the sets and therefore longer absolute rest time (P0.05). However the absolute RI in 2F (~2 min) was shorter than in I7 and IP (~3 min), which reduced the total duration of the training session. Conclusion: Determining between-set RI based on ERR instead of using fixed intervals does not enable more work to be done in multiple-set/high intensity resistance training sessions.